AI FOR SUSTAINABLE ART PRODUCTION MANAGEMENT - Mishra, Abhinav; Mahajan, Shriya; Meher, Kunal; Sahu, Badri Narayan; Agarwal, Sarika; Srivastava, Richa (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This study looks into how AI technologies can help artists to use resources more efficiently and make less waste, and make their work more eco-friendly. AI provides tools that enable not only greater creativity but also less damage that can be done to the environment by making and sharing art via AI. It does this by linking new ideas in art with environmental-friendly ways of making things. The first part of the study is an extensive review of the existing literature on the uses of AI in art and acceptance of environmentally friendly methods in creative areas such as design, digital medium, and the visual arts. A mixed approach is applied for the technique, which examines both qualitative and numeric aspects of sustainability, such as energy economy, lifetime effect of materials, and reducing carbon emissions via AI-driven actions. Some important areas of focus are optimising resources with the help of AI, making things that use less energy, and choosing smart materials according to lifecycle analysis. The paper also contains case-studies of digital art platforms that deploy AI, fashion efforts that are good for the environment, and creative AI projects that attempt to reduce waste. The results shows the potential of AI as a creative partner to be a sustainability driver. It can promote responsible innovation without compromising on art purism. The paper comes to the conclusion that the use of AI as a means to aid in making art production more sustainable is a good way for the creative economy to move towards circularity and environmental awareness.